Comparison of the G3 and G4 skating techniques in cross-country skiing - Hegge, A. M.; Holmberg, H. C.; Sandbakk, O. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The five predominant skating techniques employed in cross-country skiing can be classified from gear 1 to 5, where the skier`s speed and incline of the track determine the gear chosen. The third (G3) and fourth gears (G4) both involve symmetrical double poling, but G3 includes two poling actions per cycle (i.e., poling together with each leg pushoff) and G4 only one (i.e., poling together with the leg push-off on the strong side and a forward arm swing in combination with the leg push-off on the weak side). Our purpose was to directly compare these two techniques, which, to the best of our knowledge, has not yet been done.